Airborne pollen of Quercus in Malaga (S. Spain) and its relationship with meteorological parameters - Recio, Marta; Trigo, M. Mar; Toro, F. Javier; Cabezudo, Baltasar (Acta Botanica Malacitana, 1999)
In this work we present the airborne pollen measurements of Quercus in Málaga during the1992-1998 period. The study was carried out whit the aid of a volumetric spore-trap (Burkard seven-dayrecorder) located on the flat roof of the Faculty of Medicine, 1 km far from the city centre. We have also analysed the seasonal and intradiurnal variations and their relationship with the meteorological parametersby means of the Spearman's correlation test. This pollen type was mainly detected in the atmosphere of Málaga during March, April and May, with a maximum peak in April, excluding 1997, in which the peaktake place in March. The mean daily pollen concentrations are high (50-100 pollen grains/cubic meter ofair) to very high (>100 pollen grains/cubic meter of air) during several days, the maximum daily value detected reaching 1578 pollen grains/ m 3 in 1997. The annual total concentrations were different for thedi fferent years studied, however the Quercus pollen always became the third with relation to the others pollen types detected in Malaga. The intradiurnal variation patterns were not stable from year to year, however, in general, this taxon lightly increased at night. The correlations obtained between daily pollen concentrations and different meteorological parameters showed that the presence of this pollen type in the air of Malaga is positively associated with sunshine, temperature, speed and northwesterly wind direction; and negatively associated with calm frecuency and the others wind directions. These positive andsignificant correlations obtained with northwesterly wind show that the Quercus pollen registered in Malaga comes from inlands where the holm oaks, cork trees, and kermes oaks arc common. In Malaga, asthat occurcd in others stations of the Spanish Aerobiological Network (the REA), 1997 was the year whenthe earliest maximum peak and the higest concentrations were obtained. We think the abudant rainfalls occurred during the previous autumn contributed to the formation of high quantities of flowering buds in Quercus, and the warm temperatures detected during the following winter (February and March) to theearly maduration and opening of they.